Determination of the D0→K-π+π0 and D0→K-π+π+π- coherence factors and average strong-phase differences using quantum-correlated measurements - Lowrey, N; Mehrabyan, S; Selen, M; Wiss, J; Mitchell, R; Shepherd, MR; Besson, D; Pedlar, T; Cronin-Hennessy, D; Gao, K; Hietala, J; Kubota, Y; et al. (2009)
The first measurements of the coherence factors (RKππ0 and RK3π) and the average strong-phase differences (δDKππ0 and δDK3π) for D0→K-π+π0 and D0→K-π+π+π- are presented. These parameters can be used to improve the determination of the unitarity triangle angle γ in B-→DK- decays, where D is a D0 or D̄0 meson decaying to the same final state. The measurements are made using quantum-correlated, fully reconstructed D0D̄0 pairs produced in e+e- collisions at the ψ(3770) resonance. The measured values are: RKππ0=0.84±0.07, δDKππ0=(227-17+14)°, RK3π=0.33-0.23+0.20, and δDK3π=(114-23+26)°. These results indicate significant coherence in the decay D0→K-π+π0, whereas lower coherence is observed in the decay D0→K-π+π+π-. The analysis also results in a small improvement in the knowledge of other D-meson parameters, in particular, the strong-phase difference for D0→K-π+, δDKπ, and the mixing parameter y. © 2009 The American Physical Society.